278 Replacing cottonseed meal and sorghum grain with corn dried distillers grains with solubles in lamb feedlot diets: volatile compounds from cooked lamb chops. (5th December 2019) - Kerth, Chris R; Hodges, Kade M; Wall, Kayley R; Hicks, Zena M; Tucker, Dylan H; Whitney, Travis R; Ramsey, Wesley S; Woerner, Dale
Abstract: Dorper ram lambs (n = 46) were fed diets replacing cottonseed meal (CSM) and sorghum grain with dried distillers grains with solubles (DDGS). Lambs were fed with ad libitum access to 70.9% concentrate diets for 61 d in individual pens. The positive control diet (CNTL) contained CSM, sorghum grain, and other concentrates, but no DDGS. The four treatment diets were similar to CNTL, but did not contain CSM. Corn DDGS replaced 0%, 33%, 66% or 100% of the sorghum grain in the treatment diets. Lambs fed CNTL were contrasted to those fed 0% DDGS and linear and quadratic effects were evaluated within the four treatment diets. At 48-h postmortem, the longissimus muscle was removed from the carcass, frozen, thawed, cooked, and volatiles were collected using SPME/GC/MS. One volatile, 3-methyl, 1-butanol was greater (P = 0.03) in CNTL, while 0DDGS had effectively no volatile present. For linear effects, 1-heptanol (fruity aroma) and 2-pentyl furan (caramel aroma) tended to increase linearly (P = 0.06 and 0.05, respectively), while 2-butanone tended to decrease linearly (P = 0.06; fruity-green aroma) in chops as DDGS increased in the diet. Additionally, 2-heptanone (P = 0.02; banana aroma) and heptanol (P = 0.03; woody aroma) both increased linearly in chops as DDGS increased in the diet. In the quadratic effects, decanoic acid (ethyl ester; grape aroma) tended to decrease quadratically (P = 0.07), while 2-butanone, methyl pyrazine (meaty, roasted aroma), and 2-ethyl-5-methyl pyrazine (coffee, nutty aroma) tended to increase quadratically (P = 0.05, 0.09, and 0.08, respectively) in chops with an increase in DDGS. The volatiles 2, 5-dimethyl pyrazine (musty, cocoa aroma) and 2, 3-octanedione (warmed-over aroma) both increased quadratically (P < 0.05) in chops as DDGS increased in the diet. Except for 2, 3-octanedione, volatile aroma compounds were enhanced when DDGS replaced CSM and sorghum grain in lamb feedlot diets.